Good Governance dalam Perspektif Hukum Islam - Arief Aulia Rachman (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2010)
Governance system refers to all systems in bureaucracy which conducts its role to order the citizen. The study of governance is not only talk about a little part of it, but it refers to all important elements in a state.